Enzymatic Synthesis and Application of Palm Oil-Based Fatty Hydroxamic Acids - Suhendra, Dedy (2004)
Fatty hydroxamic acids (FHA) have been successfully synthesized from palm oils by a one-step lipase catalyzed reaction. Conversion of palm oils into the FHA was carried out by treating the substrate with hydroxylamine at 300C and neutral pH for 30 h. The method employed offers technical simplicity and easy isolation of the enzyme from the products and other components in the reaction mixture. Moreover, it also allows the reaction to be carried out under mild conditions, which reduces unwanted products. The percentages of conversion of commercial palm olein, RBD palm olein, RBD palm oil, RBD palm stearin and RBD palm kernel olein into their fatty hydroxamic acids, under the optimum conditions were 89, 79, 77, 90 and 98, respectively. The presence of the hydroxamic acid groups in the purified products was confirmed by the qualitative test, FTIR analysis, CHN elemental analysis and HPLC. Based on the ability of hydroxamic acid as a metal chelator, the synthesized FHA was used as a reagent for metal ion extraction and spectrophotometric determination. Spectrophotometry of complexes of vanadium (V) – and iron (III) – FHA shows that the molar extinction coefficient (ε) of vanadium (V) – FHA and iron (III) – FHA complexes were 6500 L mol-1 cm-1 and 9600 L mol-1 cm-1, respectively. In addition, the detection limit of vanadium (V) – FHA and iron (III) – FHA complexes were 0.001 x 10-4 and 0.008 x 10-4 M, respectively. The mole ratio for the vanadium (V) – FHA complex was 3:1 while for the iron (III) – FHA was 2:1. The FHA was also used as an extractant for recovery of copper (II) and iron (III) ions from aqueous media. Separations of copper (II) from other metal ions such as Co (II), Ni (II), Cd (II) and Zn (II) are conveniently achieved in the pH range of 4 to 6. A single extraction and stripping gave a good separation and preconcentration of copper (II) and iron (III). The separation of copper (II) can be accomplished quantitatively from other metal ions. However copper (II) cannot be quantitatively separated from iron (III) in a mixture. A preconcentration process has been proposed for the determination of copper (II) in water samples, which contains trace concentrations of copper (II), which cannot be measured directly by FAAS. It has been shown that the extraction of aqueous phase containing copper (II) with organic phase containing FHA and then stripping the organic phase with 10 % HNO3 gave a solution of copper (II) 10 fold in concentrations. Meanwhile, extraction of iron (III) from aqueous solution shows a selective extraction, in which only iron could be extracted in pH 2. The FHA synthesized from commercial palm olein was successfully immobilized onto Amberlite XAD-4 and Amberlite XAD-7 resins. The FHA loaded Amberlite XAD-4 (FHA-Amb) has been successfully used for the separation and preconcentration of copper (II) and iron (III) ions from aqueous solutions. The effect of factors such as pH, sample volume, flow rate and concentration of eluant on the preconcentration efficiency were investigated. It was found that quantitative recovery of copper (II) ion from FHA loaded Amberlite XAD-4 resin was obtained using HNO3 (10%) as eluant with a preconcentration factor up to 60. The methods for the separation of copper (II) from Zn (II) and Cd (II) have been proposed. From the separation studies of iron (III) in a solution containing Cu (II), Zn (II), Cd (II) and Ni (II) ions by FHA-Amb, it was found that only iron (III) was extracted by the resin at pH 2. This indicates that FHA is a selective chelating agent for the separation of iron (III) ion from Cu (II), Zn (II), Ni (II) and Cd (II) ions at pH 2. While, the preconcentration studies of iron (III) ion from aqueous media showed that the percentage recoveries for all preconcentration factors are 100%. This indicates that the FHA-Amb can be applied for the preconcentration of iron (III) ion in aqueous media.